The Genus Gonocephalum Solier, 1834 (Coleoptera: Tenebrionidae: Tenebrioninae) From Maharashtra With Some New Records - Hegde, V. D.; Manthen, S. V.; Kulkarni, B. (Indian Forester, 2018)
The study of the Tenebrionidae from the collections in Western Regional Centre, ZSI, Pune and earlier literature revealed the report of 16 species belonging to genus Gonocephalum under the tribe Opatrini of sub family Tenebrioninae of the family Tenebrionidae from Maharashtra state and 11 species are new records to the state and two species Gonocephalum balmeae Kaszab, 1952 and Gonocephalum cookae Kaszab, 1952 reported are endemic to Maharashtra state.